Peran Mediasi Meaning In Work : Kepemimpinan Transformasional Dan Work Engagement - Mokhammad Khukaim Barkhowa; Darwati Darwati (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Indonesian economy will face a world economic crisis. It is predicted that there will be a wave of mass layoffs when facing the global recession in 2023. In addition, today's world has changed rapidly and has entered a new environment. The purpose of this study is to examine how transformational leadership influences work engagement with meaning in work as mediation among Company employees in Salatiga City. The important thing about this research is that it can expedite the company's activities in dealing with economic recession, environmental changes and post-pandemic Covid 19. This scientific study was conducted on the workforce working in the City of Salatiga based on the Central Bureau of Statistics for the City of Salatiga, totalling 103,979 people. Due to limitations, this study's sampling was carried out using calculations with the Slovin formula with a sample size of 100 employees. The sampling method uses a probabilistic sampling method, which equals the probability that each element (member) of the population will be selected as a member of the sample. Sampling using simple random sampling, namely the collection of sample members and the population, is done randomly without regard to the layers in the population. The data analysis technique to answer the research hypothesis uses the Smart Partial Least Square (PLS) tool. The results showed that transformational leadership statistically has a positive and significant effect on work engagement, transformational leadership statistically has a positive and significant effect on meaning in work, meaning in work has a statistically positive and significant effect on work engagement, and transformational leadership has a statistically positive and significant effect on work engagement mediated by meaning in work